Utilização de volumoso extrusado contendo diferentes aditivos na alimentação de ovinos - Assis, Tamires Soares de (2019)
The enrichment of foods with ruminal fermentation modulating additives envisages an of ruminal fermentation, envisions the increase inof feed efficiency in ruminants. The objective of this work was to evaluate digestive parameters, physiological and ingestive behaviorparameters of sheep fed with Forrage ® extrudate containing different additives. The experiment was carried out at the Federal University of Uberlândia MG in the sheep and goat sector, from October 24, 2017 to November 25, 2017. It was approved by the Committee on Ethics in the Use of Animals protocol 094 /17. Twenty sheep,non-pregnant crossbred ewes (1/2 Dorper x ½ Santa Inês), aged over four years and mean body weight of 68 kg were used. The animals were housed in metabolic cages equipped with feeder, drinking fountain, salt shaker and wooden slatted floor. The sheep received five dietstreatments: Foragge® Essential® (Essential Oils); Foragge® Max® (Virginamycin); Foragge® AA (Unpurified yeast); Foragge® Bypro® (Tanino) and Foragge® Factor® (Purified Yeast), offered twice a day, 8am and 4pm. The experiment was designed in randomized blocks, blocking the effect of the phase. The means of the treatments were evaluated by the SNK test at a significance level of 595%. There was no statistical difference due to the inclusion of additives for: dry matter consumption; dry matter digestibility; Water consumption; consumption of water in relation to dry matter consumption; consumption of crude protein; crude protein digestibility; weight of faeces in natural matter, dry matter, dry matter, fecal score; urine volume; urine density; nitrogen consumption; fecal nitrogen, nitrogen retained; nitrogen retained in relation to ingested nitrogen; consumption of neutral detergent fiber; neutral detergent fiber as a function of body weight; neutral detergent fiber corrected for ash; acid detergent fiber, neutral detergent fiber digestibility, ingestive behavior, feed efficiency, respiratory rate, heart rate, rectal temperature and ruminal pH. However, the Foragge® Factor® treatment, containing purified yeast, obtained the highest values ofHowever, there was statistical differentiation for dry matter intake as a function of body weight and metabolic weight, urinary nitrogen, hemicellulose and hemicellulose as a function of NDF corrected for ash, (Foragge® Factor®), urinary nitrogen (tannin and yeast purified yeast), hemicellulose and hemicellulose as a function of NDF corrected for ashes andash, (purified yeast and oils ruminal movements. There was (yeast and essential oils), there was also a quadratic effect on the pH when the time of collection of ruminal liquidfluid was evaluated, with the lowest values of ruminal pH in the first 4 hours after the meal.